Tổng hợp và nghiên cứu hình thái, tính chất của lớp phủ PbO2 kết tủa điện hóa trên nền thép mềm và khả năng ứng dụng làm điện cực trong pin chì dự trữ - Mai Thanh, Đinh Thị; Lan, Ngô Thị; Tú, Doãn Anh; Kỳ, Nguyễn Văn (Vietnam Journal of Chemistry, 2015)
Lead dioxide electrodeposition has been caried out at constant currents from lead nitrate solution 0.5 mol/L on mild steel substrate; Fe3O4 films coating on steel substrate that prepared by electrochemical oxidation method (Fe3O4ĐH) and chemical oxidation method (Fe3O4HH) in hot alkaline solution. The morphology and structure analysis of the PbO2 layers were investigated using scaning electron microscopy (SEM) and X-ray diffraction techniques. PbO2/steel, PbO2/Fe3O4ĐH/steel, PbO2/Fe3O4HH/steel electrodes were tested the electrochemical behaviors with the role of the positive electrodes in Pb/HSiF6/PbO2 reserve battery. When synthesized in the conditions: 0.5 M Pb(NO3)2 solution, the imposed current density from 5 to 40 mA/cm2, temperature 30 °C, pH 4; PbO2 coatings formed on the mild steel substrate mainly with betta-PbO2 crystals of tetrahedral structure with different sizes and tight, solid arrangement. The best adhesion PbO2 coatings had obtained on mild steel substrate with Fe3O4 conversion layer, which formed by electrochemical methods (Fe3O4ĐH). Results of discharge test showed that the stable discharge times at maximum voltage decreased if current density, which was used in electrodeposition of PbO2 increased. In the electrodeposition of PbO2 at imposed current density of 10 mA/cm2, the obtained PbO2/Fe3O4ĐH/steel electrodes have the stable discharge times up to 390 seconds at potentials 1.69-1.7 Volts.